A 18F radiolabelled Zn(ii) sensing fluorescent probe. Issue 26 (12th March 2018) - Price, Thomas W.; Firth, George; Eling, Charlotte J.; Kinnon, Michelle; Long, Nicholas J.; Sturge, Justin; Stasiuk, Graeme J.
Abstract : A selective fluorescent probe for Zn(ii ), AQA-F, has been synthesised and radiolabelled.AQA-F exhibits a ratiometric (80 nm) shift in emission and responds to endogenous Zn(ii ) levels in vitro . Abstract : A selective fluorescent probe for Zn(ii ), AQA-F, has been synthesized.AQA-F exhibits a ratiometric shift in emission of up to 80 nm upon binding Zn(ii ) ([AQA-F ] = 0.1 mM, [Zn(ii )Cl2 ] = 0–300 μM). An enhancement of quantum yield from Φ = 4.2% to Φ = 35% is also observed.AQA-F has a binding constant, K d = 15.2 μM with Zn(ii ). This probe has been shown to respond to endogenous Zn(ii ) levels in vitro in prostate and prostate cancer cell lines.[ 18 F]AQA-F has been synthesized with a radiochemical yield of 8.6% and a radiochemical purity of 97% in 88 minutes.AQA-F shows the potential for a dual modal PET/fluorescence imaging probe for Zn(ii ).